Blocking Analysis in Optical WDM network - Kaur, Harpreet; Rattan, Munish (International Journal of Computer Sciences and Engineering, 2019)
Demand of enormous bandwidth is explosively increasing nowadays. It can be fulfilled with the use of wavelength division multiplexing technology(wdm). Using optical wdm network for data transfer applications involves establishing the light paths for the traffic requests. In this paper, traffic scheduling of irregular requests is done with the use of the hybrid heuristic technique of flower pollination and simulated annealing algorithm. Also, the effect of number of wavelength channels present is analyzed using full wavelength conversion and nil wavelength conversion capability at the intermediate nodes. The results obtained after extensive simulation proved that the wavelength count of 16 is the most optimum count of wavelength resulting in proper resource optimization. Also, the hybrid of flower pollination and simulated annealing produces more promising results relative to chaotic particle swarm optimization in the context of the blocking probability for irregular traffic.